An Automated Text Message Navigation Program Improves the Show Rate for Outpatient Colonoscopy. (December 2019) - Mahmud, Nadim; Doshi, Sahil D.; Coniglio, Mary S.; Clermont, Michelle; Bernard, Donna; Reitz, Catherine; Khungar, Vandana; Asch, David A.; Mehta, Shivan J.
Background . Numerous barriers to outpatient colonoscopy completion exist, causing undue procedure cancellations and poor bowel preparation. We piloted a text message navigation program to improve colonoscopy adherence. Method. We conducted a prospective study of patients aged 18 to 75 years scheduled for outpatient colonoscopy at an urban endoscopy center in April 2018. An intervention arm consisting of bidirectional, automated text messages prior to the procedure was compared with a usual care arm. We enrolled 21 intervention patients by phone and randomly selected 50 controls. Outcomes included colonoscopy appointment adherence, bowel preparation quality, and colonoscopy completion. Results . The arms had similar demographics and comorbidities. Intervention patients had higher colonoscopy appointment adherence (90% vs. 62%, p = 0.049). There were no significant differences in preparation quality or procedure completeness. Poststudy surveys indicated high patient satisfaction and perceived usefulness of the program. Conclusion . A bidirectional, automated texting navigation program improved colonoscopy adherence rates as compared with usual care.